Kavinia chacoserrana sp. nov. (Gomphales, Basidiomycota): a new species from South America based on morphological and molecular data - Robledo, Gerardo Lucio (2017)
Kavinia chacoserrana is described as a new species based on morphological data and molecular evidence. The species is characterized by its white to pale yellowish hydnoid hymenophore and cylindrical to fusiform basidiospores measured as 10-12 × 3-4 μm. Phylogenetic analysis provide evidence suggesting that, as currently accepted, Kavinia alboviridis is a species complex.